2011
DOI: 10.1007/s12639-011-0047-2
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and pathological lesion of Trichomonas gallinae in pigeons of Iran

Abstract: This research was conducted to determine the prevalence and pathological lesion of Trichomonas gallinae in pigeons in the northeast part of Iran. Wet mount preparations from the oral cavity/crop of 418 pigeons (Columba livia) captured from various locations in Khorasan province analyzed for T. gallinae by Giemsa's staining between April 2008 and June 2009. A total of 418 pigeons, 37.32% (n = 156) were infected with T. gallinae. Macroscopically, the oropharynx of infected pigeons has white, caseous lesions or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 20 publications
4
21
0
1
Order By: Relevance
“…The present study is apparently the first report of the occurrence of a Trichomonas in the upper digestive tract of turkey and pigeons in the southeast of Iran. In previous studies in Iran, Borji et al (2011) reported 37.32 % infection with trichomoniasis in affected pigeons of Khorasan province (Borji et al 2011). In other report from Ahvaz, Iran, Mayahi et al (2007) studied trichomoniasis in pigeons and domestic hens and detected Trichomonas from affected pigeons, but domestic hens not infected with T. gallinae (Mayahi et al 2007).…”
Section: Discussionmentioning
confidence: 97%
“…The present study is apparently the first report of the occurrence of a Trichomonas in the upper digestive tract of turkey and pigeons in the southeast of Iran. In previous studies in Iran, Borji et al (2011) reported 37.32 % infection with trichomoniasis in affected pigeons of Khorasan province (Borji et al 2011). In other report from Ahvaz, Iran, Mayahi et al (2007) studied trichomoniasis in pigeons and domestic hens and detected Trichomonas from affected pigeons, but domestic hens not infected with T. gallinae (Mayahi et al 2007).…”
Section: Discussionmentioning
confidence: 97%
“…15 The degree of change and virulence of pathological strains was low to high heterogeneity of T. gallinae causes trichomoniasis. 16 Infiltration of the trachea and lungs is associated with a severe inflammatory response to the surrounding tissue. 17 Cytopathological analysis revealed many pyriform protozoa, compatible with Trichomonas gallinae.…”
Section: Discussionmentioning
confidence: 99%
“…In the center of Iran, [35] performed a study on pigeons in which the total prevalence rate of T. gallinae was 70.09%. In a study conducted by [36] recorded infection of Columba livia collected in various locations in Khorasan province, Iran, the prevalence of T. gallinae was 37.32%, and in Isfahan, Iran. [36] recorded the prevalence 57% of T. gallinae in (Columba livia domestica) from January to June 2010.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by [36] recorded infection of Columba livia collected in various locations in Khorasan province, Iran, the prevalence of T. gallinae was 37.32%, and in Isfahan, Iran. [36] recorded the prevalence 57% of T. gallinae in (Columba livia domestica) from January to June 2010. In a study monitoring the annual variation of T. gallinae infection for six years in doves a 5.6% of the mourning doves were seen to be positive for T. gallinae [38].…”
Section: Discussionmentioning
confidence: 99%